2010
DOI: 10.3402/polar.v29i3.6077
|View full text |Cite
|
Sign up to set email alerts
|

Status of the black-legged kittiwake (Rissa tridactyla) breeding population in Greenland, 2008

Abstract: Based on the intensified survey efforts (since 2003) of Greenlandic breeding colonies of black-legged kittiwake (Rissa tridactyla), the total Greenland breeding population was estimated at roughly 110 000 breeding pairs, constituting about 4% of the total North Atlantic breeding population. This population estimate of black-legged kittiwake is the most reliable and updated estimate hitherto reported for Greenland. The results confirm considerable population declines in many areas of West Greenland. The breedin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The proportion of declining colonies was higher in period 1991-2000 (average: 66%, 95% CI: 60%-73%) than in [1975][1976][1977][1978][1979][1980][1981][1982][1983][1984][1985][1986][1987][1988][1989][1990] (average: 44%, 95% CI: 38%-50%) and 2001-2010 (average: 58%, 95% CI: 52%-64%), but confidence intervals overlapped between periods 1991-2000 and 2001-2010. 3.2 | Temporal changes in the spring SST effects on kittiwake colony size Previous results indicated that kittiwake decline was more pronounced when spring SST was rapidly warming. Outside the periods of rapid ocean warming, the association between ocean warming and kittiwake dynamics was weaker (Figures 2 and 4) (Frederiksen, Wanless, Harris, Rothery, & Wilson, 2004;Labansen, Merkel, Boertmann, & Nyeland, 2010;Sandvik et al, 2014). Changes in kittiwake population trends tracked changes in trends of spring SST around the colonies and when the ocean warming was faster, the decline in kittiwake colony size was steeper.…”
Section: Descamps Et Almentioning
confidence: 99%
“…The proportion of declining colonies was higher in period 1991-2000 (average: 66%, 95% CI: 60%-73%) than in [1975][1976][1977][1978][1979][1980][1981][1982][1983][1984][1985][1986][1987][1988][1989][1990] (average: 44%, 95% CI: 38%-50%) and 2001-2010 (average: 58%, 95% CI: 52%-64%), but confidence intervals overlapped between periods 1991-2000 and 2001-2010. 3.2 | Temporal changes in the spring SST effects on kittiwake colony size Previous results indicated that kittiwake decline was more pronounced when spring SST was rapidly warming. Outside the periods of rapid ocean warming, the association between ocean warming and kittiwake dynamics was weaker (Figures 2 and 4) (Frederiksen, Wanless, Harris, Rothery, & Wilson, 2004;Labansen, Merkel, Boertmann, & Nyeland, 2010;Sandvik et al, 2014). Changes in kittiwake population trends tracked changes in trends of spring SST around the colonies and when the ocean warming was faster, the decline in kittiwake colony size was steeper.…”
Section: Descamps Et Almentioning
confidence: 99%
“…100 Recent changes in sea ice regimes (both in extent and duration) are providing opportunities for this region to host larger seabird populations (e.g., kittiwakes Rissa tridactyla and common eiders Somateria mollissima) and for the establishment of new breeding species-like black-backed gulls Larus marinus and Larus fuscus. [101][102][103][104] The kittiwake nicely illustrates the ongoing changes in range shifts for widespread species: its populations are increasing and its distribution range is expanding in the Arctic, while they are simultaneously declining in Europe at the southern border of its range. 102,103,105 The first records of gray seals Halichoerus grypus in southern Greenland, harbor porpoise Phocoena phocoena in Svalbard and well-documented shifts in gray whale Eschrichtius robustus distribution suggest that range shifts are also occurring quite broadly among marine mammals that are resulting in traditionally more southerly species spending more time in the Arctic as well as regular Arctic migrants staying for longer periods.…”
Section: Poleward Changes In Habitat and Species Distributions: A Larmentioning
confidence: 99%
“…[101][102][103][104] The kittiwake nicely illustrates the ongoing changes in range shifts for widespread species: its populations are increasing and its distribution range is expanding in the Arctic, while they are simultaneously declining in Europe at the southern border of its range. 102,103,105 The first records of gray seals Halichoerus grypus in southern Greenland, harbor porpoise Phocoena phocoena in Svalbard and well-documented shifts in gray whale Eschrichtius robustus distribution suggest that range shifts are also occurring quite broadly among marine mammals that are resulting in traditionally more southerly species spending more time in the Arctic as well as regular Arctic migrants staying for longer periods. 41 Another consequence of the reduction of sea ice is that many islands currently connected to the mainland by ice bridges for most of the year will become ice free for a longer period.…”
Section: Poleward Changes In Habitat and Species Distributions: A Larmentioning
confidence: 99%